Distribution in Chile and colonization in cayumapu river (Valdivia) of the invasive aquatic macrophyte limnobium laevigatum Distribución en Chile y colonización del río cayumapu (Valdivia) por el macrófito acuático invasor limnobium laevigatum - Martín, Cristina San; Contreras, Domingo; Vidal Ojeda, Osvaldo Javier; Solís, José Luis; Ramírez, Carlos (My University, 2021)
Limnobium laevigatum is an invasive aquatic herb that increases its range in Chile to displace native species from its place in the coastal zonation of the fresh water bodies. Seasonal biomass production and reproduction of this species are studied in the Sanctuary of Nature "Carlos Anwandter" in Valdivia, Chile. The change experienced by the coastal zonation of the river is established due to the aggressiveness of this invasive species, which was favored by the eutrophication of the waters. The average annual biomass reaches 6,140 kg/ha. The organs with the greatest contribution to biomass are the emergent leaves and the roots. Biomass production was higher in summer and lower in spring, when high values ​of necromass were also measured, indicating the presence of an unknown deleterious factor. The biomass of roots and emerging leaves has the same seasonal route with a decrease in spring, while the swimming leaves and the necromass show an inverse behavior. The presence of flowers and fruits was confirmed, which supports the hypothesis proposed of sexual reproduction for the Valdivian populations. Finally, a phenological diagram indicates the presence of viable fruits and seeds throughout the year.
Keywords: biomass; phenology; reproduction; site requirements